2019
DOI: 10.1080/15384101.2019.1612698
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calcium uniporter complex modulation in cancerogenesis

Abstract: Aberrations in mitochondrial Ca 2+ homeostasis have been associated with different pathological conditions, including neurological defects, cardiovascular diseases, and, in the last years, cancer. With the recent molecular identification of the mitochondrial calcium uniporter (MCU) complex, the channel that allows Ca 2+ accumulation into the mitochondrial matrix, alterations in the expression levels or functioning in one or more MCU complex members have been linked to different cancers and cancer-related pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 118 publications
0
32
0
Order By: Relevance
“…Previous studies on the mitochondrial Ca 2+ uniporter (MCU) complex indicated that the level of mtCa 2+ is an important determinant in the progression of different cancer types ( Marchi et al, 2019a ; Marchi et al, 2013 ; Marchi et al, 2019b ; Tosatto et al, 2016 ). The downregulation of MCU and subsequent reduction of mtCa 2+ uptake correlated with resistance to apoptosis of colorectal cancer cell lines ( Marchi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the mitochondrial Ca 2+ uniporter (MCU) complex indicated that the level of mtCa 2+ is an important determinant in the progression of different cancer types ( Marchi et al, 2019a ; Marchi et al, 2013 ; Marchi et al, 2019b ; Tosatto et al, 2016 ). The downregulation of MCU and subsequent reduction of mtCa 2+ uptake correlated with resistance to apoptosis of colorectal cancer cell lines ( Marchi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the few studies that have directly assessed the intrinsic role of mitochondrial Ca 2+ in the regulation of the cancer cell energetic status have depicted a complex scenario that mainly involves aberrant expression or function of the mitochondrial calcium uniporter (MCU) complex [59] ( Fig. 4 ).…”
Section: Mitochondria-dependent Regulation Of Malignant Energetic Stamentioning
confidence: 99%
“…Mitochondrial calcium homeostasis is essential for cell survival and metabolic regulation [60,61]. Therefore, mitochondria play a dual role in death and survival, and dysregulation of mitochondrial Ca 2+ -homeostasis is associated with various diseases including cancer [62]. Importantly, mitochondrial calcium uniporter (MCU) is the channel enabling accumulation of Ca 2+ in the matrix [62].…”
Section: [Ca2+]i -Signaling In Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Therefore, mitochondria play a dual role in death and survival, and dysregulation of mitochondrial Ca 2+ -homeostasis is associated with various diseases including cancer [62]. Importantly, mitochondrial calcium uniporter (MCU) is the channel enabling accumulation of Ca 2+ in the matrix [62]. Aberrant expression or functioning of MCU complex contributes to cancer [62].…”
Section: [Ca2+]i -Signaling In Cell Proliferation and Apoptosismentioning
confidence: 99%